In vitro modelling of the physiological and diseased female reproductive system. (15th September 2021) - Stejskalová, Anna; Vankelecom, Hugo; Sourouni, Marina; Ho, Magdalene Y; Götte, Martin; Almquist, Benjamin D
Abstract: The maladies affecting the female reproductive tract (FRT) range from infections to endometriosis to carcinomas. In vitro models of the FRT play an increasingly important role in both basic and translational research, since the anatomy and physiology of the FRT of humans and other primates differ significantly from most of the commonly used animal models, including rodents. Using organoid culture to study the FRT has overcome the longstanding hurdle of maintaining epithelial phenotype in culture. Both ECM-derived and engineered materials have proved critical for maintaining a physiological phenotype of FRT cells in vitro by providing the requisite 3D environment, ligands, and architecture. Advanced materials have also enabled the systematic study of factors contributing to the invasive metastatic processes. Meanwhile, microphysiological devices make it possible to incorporate physical signals such as flow and cyclic exposure to hormones. Going forward, advanced materials compatible with hormones and optimised to support FRT-derived cells' long-term growth, will play a key role in addressing the diverse array of FRT pathologies and lead to impactful new treatments that support the improvement of women's health. Statement of significance: The female reproductive system is a crucial component of the female anatomy. In addition to enabling reproduction, it has wide ranging influence on tissues throughout the body via endocrine signalling. This intrinsic role in regulating normal female biology makes it susceptible to a variety of female-specific diseases. However, the complexity and human-specific features of the reproductive system make it challenging to study. This has spurred the development of human-relevant in vitro models for helping to decipher the complex issues that can affect the reproductive system, including endometriosis, infection, and cancer. In this Review, we cover the current state of in vitro models for studying the female reproductive system, and the key role biomaterials play in enabling their development. Graphical abstract: Image, graphical abstract